Construction and stability evaluation of ecological networks in the Loess Plateau - Liangjie Yang; Fangning Zhang; Lishuang Qin (Ecological Indicators, 2024)
Enhanced and optimized ecological security patterns in ecologically fragile areas are conducive to promoting their sustainable development. A valuable strategy for achieving multi-dimensional coexistence and stability of regional functions is constructing ecological networks and optimizing them. Given its susceptibility to human activities and climate change, enhancing the ecological security pattern of the Loess Plateau is particularly crucial. This study selects nine indicators from natural and human activity perspectives and constructs an ecological network using MCR and gravity models. Then, complex network analysis is performed to examine the ecological network topology and stability under deliberate attacks and random failures in the Loess Plateau. The results indicate that ecological sources are primarily located in the central and northern regions of the Loess Plateau, and the links adhere to the proximity effect theory, displaying an inverse relationship with the spatial distance separating the sources. Both preferential attachment and a power-law distribution are observed in the degree distribution of the ecological network. Additionally, deliberate attacks and random fault simulations lead to a significant decrease in both connectivity and transmission efficiency of the ecological network. The failure of hub nodes exerts a diverse range of influences on the ecological network. This study enhances our understanding of ecosystem interactions and presents crucial insights for ecological conservation and restoration strategies.